IPSS does not impact management in Cushing's Disease when a pituitary tumor is visible on MRI - Michelle D. Lundholm; Kevin M. Pantalone; Pratibha PR Rao; Amir H. Hamrahian; Varun R. Kshettry; Pablo Recinos; Divya Yogi-Morren (Endocrine and Metabolic Science, 2025)
Purpose: There is controversy surrounding the value of inferior petrosal sinus sampling (IPSS) in Cushing's Disease (CD) when there is a visible pituitary lesion on pre-operative imaging. This study compares lateralization results between IPSS and pituitary MRI against surgical localization. Methods: A retrospective chart review was conducted at a tertiary referral center on patients with pathology-confirmed CD between 2003 and 2022, with unilateral pituitary tumor on MRI, and successful pre-operative bilateral IPSS. Bilateral sellar exploration was performed surgically in all cases. Results: Of 32 patients included, all had IPSS results consistent with CD and all lateralized. The median age at diagnosis was 43 years (range 23–69 years) and 88 % were female (N = 28). The median tumor size on MRI was 5 mm (range 3–12 mm). Prolactin adjustment was performed in the interpretation of IPSS in 30 cases (94 %). MRI correctly lateralized 31 tumors (97 %), whereas IPSS correctly lateralized 27 tumors (84 %). Of the 6 cases where MRI and IPSS disagreed on laterality, the operative report was consistent with MRI lateralization in 4 of 6 cases, and midline disease in the remaining 2 cases. There were no cases where IPSS lateralization was correct when MRI lateralization was incorrect. Conclusion: When a tumor is visible on MRI (≥3 mm), IPSS does not add to the accuracy of determining tumor lateralization. Therefore, IPSS does not add to the diagnostic nor therapeutic management for patients with biochemical testing consistent with CD and visible tumor on MRI.